Health safety knowledge in Portugal and Spain - Rodrigues, D. L.; Carvalho, A. C.; Lopes, D.; Garrido, M. V.; Richard de Visser; Rhonda Nicole Balzarini; Prada, M. (The Social Observatory, 2022)
Reports have shown a decline in condom use and an increase in sexually transmitted infections (STIs) worldwide. For example, an increasing number of adolescents in Portugal and Spain failed to consistently use condoms between 2002 (10%) and 2018 (20%), and STIs rates in 2019 had increased, on average, 40% since 2015 in Europe. This indicates that many people lack adequate knowledge or fail to enact sexual health behaviours regularly, therefore increasing the risk of negative health consequences. This article examines how being motivated by disease prevention (“safety”) or pleasure promotion (“pleasure”) shapes the way people construe sexual health and pursue their sexual goals. Participants were categorised into each group based on their responses to the Regulatory Focus in Sexuality Scale (364 participants focused on safety; 378 participants focused on pleasure) and asked a series of questions regarding their knowledge about 13 STIs, past testing practices, use of contraceptive methods, and beliefs about condoms. Results show the importance of individual motives in sexuality in modulating different facets of sexual health. This research can help inform the development of new theoretical perspectives, evidence-based interventions, or education programmes aimed at increasing sexual health literacy to help curb this public health concern in Portugal and Spain.